Sex ratio and abundance fluctuations of sarcosaprophagous calyptratae (Diptera): Field evaluation of two sampling techniques - Mulieri, Pablo Ricardo (2018)
Abundance of sarcosaprophagous Calyptratae species was monitored by using baited traps and active captures with hand net. Analysis of field data collected in three protected areas in the Valdivian temperate forest of South America (Lanín National Park, Lago Puelo National Park, and Los Alerces National Park) indicated that bottle traps baited with putrescine is a reliable method to estimate local abundance of sarcosaprophagous species by comparison to the active capture method. Also, we describe and compare general patterns of sex bias for four dominant species: Sarconesia magellanica (Le Guillou), Calliphora vicina Robineau-Desvoidy, Microcerella spinigena (Rondani), and Oxysarcodexia varia (Walker). From these analyses, it can be concluded that abundance fluctuations of flies showed significant relationship between the sampling methods. This study showed that besides the expected interspecific differences in trapping efficiency, there are acute intraspecific differences of sex ratios between sampling methods.